Propuesta alternativa de coagulantes naturales (2021)
For any living being on earth, water is the most important natural resource. For this reason, water must be potable to avoid alterations and diseases in humans and living beings that consume it. In the purification of water, artificial coagulants are usually used, such as Aluminum Sulphate, which produces diseases such as Alzheimer’s disease in the long term. The offer of an alternative that eliminates the use of artificial coagulants for the purification of the water, allows the reduction of affectations to the human being. The use of products such as moringa and broad bean, act as natural coagulants, with a previous process such as grinding, maceration and sieving of the products before they act in the water or in the potabilization of it. In this process, the natural or non-conventional coagulants were implemented in two ways, type infusion and added directly to the guide using concentrations such as for the bean of 6 and 9 grams, for the moringa 5 grams and the union of the two coagulants with a concentration of 6 grams. In all cases, 1000 ml of water was used. The water samples that were used for the analysis were taken from the Andean biome called Lago de Tota, located in the municipality of Aquitania (Boyacá). It is important to note that the coagulants were left to be treated for 24 hours, without any type of movement.